1994
DOI: 10.1128/iai.62.12.5689-5693.1994
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial heat shock proteins directly induce cytokine mRNA and interleukin-1 secretion in macrophage cultures

Abstract: Bacterial heat shock proteins (hsp) have been shown to be important immunogens stimulating both T cells and B cells. However, little is known concerning the direct interactions between hsp and macrophages. In this study, we demonstrated that treatment of macrophage cultures with purified bacterial hsp, including Legionelia pneumophila hsp6O, Escherichia coli GroEL, Mycobacterium tuberculosis hsp7O, Mycobacterium leprae hsp65, and Mycobacterium bovis BCG hsp65, increased the steady-state levels of cytokine mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(79 citation statements)
references
References 29 publications
0
79
0
Order By: Relevance
“…The chaperon function of Hsp is of major importance for protein synthesis; the ubiquitous distribution of Hsp and their high sequence conservation pose interesting challenges to the immune system. During macrophage activation, in which a wide variety of polypeptides are induced, increased levels of Hsp (both mRNA and proteins) are produced [34]. The diet composition may, by altering lymphocyte activation, have a high in£uence on autoimmune processes.…”
Section: Discussionmentioning
confidence: 99%
“…The chaperon function of Hsp is of major importance for protein synthesis; the ubiquitous distribution of Hsp and their high sequence conservation pose interesting challenges to the immune system. During macrophage activation, in which a wide variety of polypeptides are induced, increased levels of Hsp (both mRNA and proteins) are produced [34]. The diet composition may, by altering lymphocyte activation, have a high in£uence on autoimmune processes.…”
Section: Discussionmentioning
confidence: 99%
“…It has already been shown that this low LPS concentration does not induce IL-1b mRNA expression or enhance the expression when added to Lp-hsp 60. 27 In order to further minimize the possible influence of any remaining endotoxin, the Lp-hsp 60 was always diluted in RPMI-1640 medium containing 16 m g/ml polymyxin B. This treatment has been shown to completely neutralize 20 ng of LPS per ml in terms of IL-1b mRNA inducing activity under the experimental conditions chosen.…”
Section: Evaluation Of Lp-hsp 60 Preparation For the Presence Of Lpsmentioning
confidence: 99%
“…It has been shown that various bacterial hsp directly induce increased cytokine mRNA accumulation in macrophages. 27 Thioglycollate-elicited macrophages from BALB/c mice were stimulated with Lp-hsp 60 (5 m g/ml) for 3 hr. The RNA was extracted, reverse transcribed and amplified by PCR as described above.…”
Section: Cellular Il-1b Mrna Steady-state Levels After Stimulation Wimentioning
confidence: 99%
See 2 more Smart Citations